Governing Precarious Immigrant Workers in Rural Localities: Emerging Local Migration Regimes in Portugal - Inês Cabral; Thomas Swerts (Politics and Governance, 2021)
Over the last decades, the globalization of the food and agriculture sector has fueled international labor migration to rural areas in Southern Europe. Portugal is no exception to this trend, as the intensification of foreign investment in agriculture combined with a declining and ageing workforce created a demand for flexible immigrant labor. The Eastern European and Asian immigrant workers who answered the industry’s call were confronted with poor working conditions and lacking access to public services. In this article, we zoom in on the governance challenge that the presence of precarious immigrant workers (PIWs) poses to rural municipalities in the south of Portugal. The burgeoning literature on local integration policies mainly focuses on how cities deal with the challenge posed by international labor migration. This article draws on a detailed case study of the municipality of Odemira to argue that more attention needs to be paid to emerging local migration regimes in non-urban localities. By adopting a regime-theoretical approach, we study how power relations between the local government, civil society, and the private sector play out around the question of immigrant reception. Our study suggests that immigration policies in rural localities are increasingly being developed through cooperation and coproduction between public and private actors. First, we demonstrate how the presence of PIWs is perceived as a policy “problem” by each actor. Second, we outline how a governing coalition formed around the shared concern to improve arrival infrastructures, stimulate integration, mediate socio-cultural impact, and accommodate business interests. We conclude by critically questioning the impact that emerging local migration regimes have on the rights and social position of PIWs in rural contexts.